If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(5x + 4) = 9x + -26 Reorder the terms: 3x(4 + 5x) = 9x + -26 (4 * 3x + 5x * 3x) = 9x + -26 (12x + 15x2) = 9x + -26 Reorder the terms: 12x + 15x2 = -26 + 9x Solving 12x + 15x2 = -26 + 9x Solving for variable 'x'. Reorder the terms: 26 + 12x + -9x + 15x2 = -26 + 9x + 26 + -9x Combine like terms: 12x + -9x = 3x 26 + 3x + 15x2 = -26 + 9x + 26 + -9x Reorder the terms: 26 + 3x + 15x2 = -26 + 26 + 9x + -9x Combine like terms: -26 + 26 = 0 26 + 3x + 15x2 = 0 + 9x + -9x 26 + 3x + 15x2 = 9x + -9x Combine like terms: 9x + -9x = 0 26 + 3x + 15x2 = 0 Begin completing the square. Divide all terms by 15 the coefficient of the squared term: Divide each side by '15'. 1.733333333 + 0.2x + x2 = 0 Move the constant term to the right: Add '-1.733333333' to each side of the equation. 1.733333333 + 0.2x + -1.733333333 + x2 = 0 + -1.733333333 Reorder the terms: 1.733333333 + -1.733333333 + 0.2x + x2 = 0 + -1.733333333 Combine like terms: 1.733333333 + -1.733333333 = 0.000000000 0.000000000 + 0.2x + x2 = 0 + -1.733333333 0.2x + x2 = 0 + -1.733333333 Combine like terms: 0 + -1.733333333 = -1.733333333 0.2x + x2 = -1.733333333 The x term is 0.2x. Take half its coefficient (0.1). Square it (0.01) and add it to both sides. Add '0.01' to each side of the equation. 0.2x + 0.01 + x2 = -1.733333333 + 0.01 Reorder the terms: 0.01 + 0.2x + x2 = -1.733333333 + 0.01 Combine like terms: -1.733333333 + 0.01 = -1.723333333 0.01 + 0.2x + x2 = -1.723333333 Factor a perfect square on the left side: (x + 0.1)(x + 0.1) = -1.723333333 Can't calculate square root of the right side. The solution to this equation could not be determined.
| -1+y=2 | | (-2)-(-7)= | | 2(-2-3v)=-4-6w | | -11.1x=88.8 | | x^2-15x+56.25=0 | | 4n--7=5-2n | | x/4-1=-6 | | 5(p+6)=9x | | c=x+0.06x+0.15x | | 4x-5-13x=-32 | | 2+6a=5 | | 7(m+6)=98 | | -16/4= | | 4(x-3)=-52 | | 5x+8=3x+58 | | -5.89x+7.5=2.18 | | -37+x=-6(7x-1) | | -5(4x+3)-9=-3(-3x+6) | | 2+3[4+2(2)]= | | 33*5*-2= | | 0.6a+4=10 | | 4y-20=12y+2 | | -5=12 | | 0.3x-0.9(6-x)=-1.2 | | 2r-(5-r)=13-2r | | 33*x*y= | | 24+4(z-4)=6z-2 | | 5y-8=y-22 | | 2(0.78+0.4x)=0.01x | | 14=(-2k)+3 | | 2m+1/2(m-4)=9 | | -9(4b+1)+(37b-6)=0 |